A new species of Australian frog (Myobatrachidae: Uperoleia) from the New South Wales mid-north coast sandplains - Clulow, Simon; Anstis, Marion; Keogh, J. Scott; Catullo, Renee A. (Zootaxa, 2016)
The discovery of new vertebrate species in developed countries is still occurring at surprising rates for some taxonomic groups, especially the amphibians and reptiles. While this most often occurs in under-explored areas, it occasionally still happens in well-inhabited regions. We report such a case with the discovery and description of U. mahonyi sp. nov., a new species of frog from a highly populated region of New South Wales, Australia. We provide details of its morphology, calls, embryos and tadpoles, and phylogenetic relationships to other species of eastern Uperoleia. We also provide the results of targeted surveys to establish its distribution and provide observations of its habitat associations. As a consequence of these surveys, we comment on the likely restricted nature of the species’ distribution and habitat, and place this in the context of a preliminary assessment of its putative conservation status, which should be assessed for listing under the IUCN’s red list. We note this species, which is morphologically distinct, has gone unnoticed for many decades despite numerous ecological surveys for local development applications.